EKSTENSIFIKASI AGRARIA SEKITAR HUTAN, DILEMA KEBUTUHAN LAHAN USAHATANI DAN TERPINGGIRNYA EKSISTENSI MASYARAKATNYA - Roosganda Elizabeth (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Degradation and forest damage that happened effect and illegal logging, and governmental policy failure effect in forest resource management. The failure made legitimation power base by for the sake of development project, although the loss of biggest ethics as people prosperity accomplishment risk. This paper aim to propose factors determining failure or efficacy [of] a[n public policy in forest resource management and development program. Forest management by private sector and state (HPH) in Indonesia, at be situation that very concern, because break of the rules destroyed forest. Forest domination resource rights enforcing as mastered by state, making agraria forest function have dregs from its as requirement accomplishment local society live effort for traditional agriculture. Empowerment represent goals which will be reached, which can be existed with existence participate from community forest. Community forest participate very determine failure or efficacy of public program in development policy, and represent tool to reach enableness. The importance of people forest take care and remain order to own benefit looking into people forest by holistic in order to the development program target more conducive, usable so that as base to rebuild forestry world which have destroyed, and also maintain and and function continueing forever and ever